FREQUENCY OF HEPATITIS B VIRUS SURFACE ANTIGEN AND HEPATITIS C VIRUS ANTIBODIES IN PEDIATRIC PATIENTS WITH MULTIPLE TRANSFUSIONS - Hayat, Mohsin; Irshad, Mohammad; Ullah, Ihsan; Khan, Kashif Ali (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the frequency of hepatitis B virus surface antigen (HBsAg) and hepatitis C virus (HCV) antibodies in children with hematological disorders having multiple transfusions. Methodology: This descriptive cross-sectional study was conducted in the Department of Pediatrics, Lady Reading Hospital, Peshawar from December 10, 2016 to June 10, 2017. A total of 230 children with different hematological disorders who received two or more blood transfusions during the past two years were included in the study. Each child was screened for HBsAg and anti-HCV antibodies using 3rd generation commercial ELISA micro-plate kits (DIA.PRO, ITALY) according to the manufacturer instructions. Results: Out of 230, 122 (53%) patients were males and 108 (47%) were females. Their mean age was 10 ±10.86 years. In this study, 23% of patients were positive for anti-HCV antibodies, while 7% of patients were positive for HBsAg. Out of 53 patients positive for hepatitis C antibodies, 55% were males. Similarly, out of 16 patients positive for HBsAg, 56% were males. Conclusion: The frequency of anti-HCV antibodies was 23% and HBsAg was positive in 7% of all children who received multiple transfusions in the past two years.